SINTESIS ANALOG 4-BROMO PIRAZOLIN DARI KALKON INTI NAFTALEN DENGAN KATALIS ASAM DAN UJI AKTIVITAS NYA SEBAGAI ANTIBAKTERI - Desy Hariyanti; Hilwan Yuda Teruna; Jasril ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Pyrazolines have been reported to possess various biological activities such as antimicrobial, antidepressant, antidiabetic, anti-inflammatory, antipyretic, anticancer, and anticonvulsant activity. In this research, a halogenated pirazoline 5-(4-bromophenyl)-3-(naphthalene-1-yl)-4,5-dihydro-1H-pyrazole was synthesized by cyclization reaction between chalchone with hydrazine hydrate using acetate acid as catalyst under microwave irradiation. The compound showed a good yield, and then was characterized by UV, IR, 1H-NMR, and 13C-NMR spectroscopy. The antibacterial activity of pyrazolines was determined using the agar diffusion method against Gram-negative bacteria: Escherichia coli and Salmonella typhi and Gram-positive bacteria: Bacillus subtilis and Staphylococcus aureus. This compound showed inhibitory activity against those four bacteria. Test results of antibacterial activity indicated that pyrazoline analogues were potential as antibiotics.